The interpretation of the folk-dancing melodies in the creation of native composers. (Pedagogy of Higher and Secondary Education, 2006)
In article the modem tendencies and peculiarities of murpretatnm of folk dancing melodies in the creation of Ukrainian composers are considered. Various forms of using folklore sources in professional music of the past and die present are analyzed.
Keywords: interpretation; dancing melodies; folklore; composer; musical work